海外文字緣——清代中日筆談交流研究: Overseas Acquaintance via Writing: A Study of Sino-Japanese Exchanges in "Brush Talks" of the Qing Period - 王曉秋 (人文中國學報, 2010)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 筆談又稱筆話、筆語，就是用筆寫文字代替口説語言進行交談。用毛筆寫漢字交談則是東亞漢字文化圈各國人士之間一種特殊的文化交流方式。特別在清代，是中日文人筆談的最盛期。由於筆談寫在紙上，往往可以保存流傳下來。故而至今在日本和中國的一些圖書館、檔案館以及民間私人文書中，還收藏有相當數量的清代中日筆談記録原本。這些筆談爲研究中日文化交流史提供了大量既珍貴又有趣的原始資料。清代中日筆談具有原始性，真實性，內容的多樣性、廣泛性，以及互動性、趣味性等特點。本文根據筆者多年的收集和研究，著重解剖日本儒者與中國漂流民的筆談《得泰船筆語》、日本藩士與上海文人的筆談《沒鼻筆語》、日本漢學家與中國駐日使館外交官的筆談《大河內文書》等幾種清代不同時期、不同地點、不同身份、不同內容的典型筆談資料，介紹這些筆談的歷史背景與由來，分析其內容，評述其意義，從而進一步論述清代中日筆談交流的特點及其史學、文學價值。 The concept of bitan, also bihua or biyu——literally, “talks through the writing brush” (hereafter “brush talks”), refers to a particular kind of writing activity that can function as a form of conversation in lieu of oral language. Conducting conversations with the writing brush is a special means of cultural exchange adopted in East Asian countries within the “Sinograph-oriented cultural circle.” The Qing dynasty (1644-1911) witnessed a climax of the “brush talk” tradition. The content of “brush talks” was written on paper and could be preserved. For this reason, a considerable number of brush talks’ produced during exchanges between China and Japan are now preserved in Chinese and Japanese libraries, archives, establishments, and private collections. These are precious and entertaining materials for research on the history of Sino-Japanese cultural exchange. Qing-dynasty “brush talks” embody marked features, such as originality, veritability, varied contents, interactivity, and amusement. The present essay is an outcome of many years of data collection and study of the topic. Its foci of examination include three collections of “brush talks”. The first one is Detaichuan biyu, a collection of “brush talks” recording conversations between Japanese Confucian scholars and Chinese vagrants. The second is Meibi biyu, a collection of “brush talks’’ between delegates of certain Japanese suzerains and Shanghai intellectuals. The third is Daihenei wenshu, a collection of “brush talks" between Japanese Sinologists and Chinese diplomats stationed in the Chinese embassy in Japan. These three collections are representative, as they were all produced during the Qing but at different points of time, in different places, by different hands (i.e., hierarchies), and with different content. The present essay introduces their historical backgrounds, analyzes their content, and evaluates their significance. It also discusses the characteristics of the exchanges in Sino-Japanese “brush talks” of the Qing period, and their value in historiography and literary studies.